Deceptive counterfeiting and purchase intention towards products in anti-counterfeit packaging: An empirical investigation in Sub-Saharan Africa - Thomas Dobbelstein; Paul Mfopou Pepuere (Journal of Applied Leadership and Management, 2019)
Research questions: What are the perceived risks factors that affect the consumer decisionmaking process in Sub-Saharan Africa? Are perceived risks useful predictor of the price acceptance of products in anti-counterfeit packaging? Methods: Empirical study with a strong focus on Sub-Saharan Africa based on 407 online consumer interviews about their risk perception for specific counterfeit product categories and their price acceptance of products in anticounterfeit packaging. Results: Although the analysis shows that perceived risks occur in the consumer decision-making process in Sub-Saharan Africa, there is no relationship between the perceived risks associated with counterfeit products occurring and the price acceptance of products in anti-counterfeit packaging.
Keywords: 650